Teknis Perpajakan bagi Perusahaan yang Mengalami Kepailitan di Indonesia - Kinara Mamora (UNES Law Review, 2023)
This journal discusses the technical taxation issues related to companies undergoing bankruptcy. Companies experiencing bankruptcy are still required to report and pay taxes as usual, albeit with some differences in the conditions before bankruptcy occurs. During the bankruptcy period, the company must continue to pay taxes on the income received during its operational period, even though in bankruptcy, the company will prioritize repaying all debts to creditors. Various taxes still need to be paid in the situation of a bankrupt company, including Value Added Tax (VAT), Property Tax (PBB), and Income Tax. Companies undergoing bankruptcy also need to prepare Annual Tax Reports, which are mandatory, with tax rates varying depending on the type of reported income. Taxation issues are crucial in the context of companies experiencing bankruptcy. Companies must understand and manage their tax obligations well, even in bankruptcy.